Influence of Drought Applied at Different Growth Stages on Kernel Yield and Quality in Maize (Zea Mays L.). Issue 19 (27th October 2016) - Anwar, Saba; Iqbal, Muhammad; Akram, Hafiz Muhammad; Niaz, Mubashir; Rasheed, Rizwan
ABSTRACT: Drought severely affects yield and its quality in different plants. In a field experiment, maize was exposed to drought stress at vegetative, silking, and kernel-filling growth stages to determine the drought-induced changes in kernel yield and quality traits. The experiment was laid-out in a randomized complete block design with four replications. Withholding water at the vegetative stage was very effective in increasing protein, total amino acids, total soluble sugars, glucose, and sucrose contents in maize kernels. In contrast, drought applied at the kernel-filling stage increased the total free amino acids, total phenolics, and activities of catalase (CAT) and ascorbate peroxidase (APX) in maize kernels. Drought at the vegetative stage improved the kernel quality while at the silking stage severely affected kernel yield in maize. Taken together, the results suggested that incidence of drought should be avoided at the silking stage to minimize kernel yield losses and decrease in kernel quality in maize.